Recent evidence-based developments in the treatment of DID - Bachrach, N.; Huntjens, R. J. C. (Frontiers in Psychiatry, 2025)
The research field focusing on the etiology, diagnosis and treatment of people with dissociative identity disorder (DID) is still relatively young and limited in scope. Until a few years ago, psychotherapeutic treatment for adults with DID consisted primarily of practice-based, phase-based psychodynamic psychotherapy based, whose treatment effects on dissociative symptoms are small. In recent years, fundamental research on dissociative amnesia and identity functioning has forwarded new insights important for the conceptualization of DID. In light of these emerging insights, empirically supported treatment modalities that have a strong evidence base in adjacent clinical populations have been adapted for application in individuals with DID. Initial results of first empirical studies have indicated positive outcomes, with large effects on dissociative symptoms, of several new treatment options. This review provides an overview of the theoretical models for DID and the foundational research that has led to the development of these models and contributed to adapting treatments with a strong evidence-base in adjacent populations to treat patients with DID. These applications show promising results among individuals with DID. An important next step for the near future is to systematically replicate and extend the evidence base of these promising new approaches in methodologically well-designed and comparative treatment studies. High-quality research is thus urgently needed to identify (cost-)effective treatment options for this population.